Resistance in Kretinga, Telšiai and Mažeikiai Counties during the First Soviet Occupation Period (1940–1941) - Rukšėnas, Alfredas (Genocidas ir rezistencija, 2009)
The article deals with the resistance in Kretinga, Telšiai and Mažeikiai counties during the period of the first Soviet occupation (1940–1941). The two periods of resistant underground activity and development are distinguished. The first covered the period from the beginning of the Soviet occupation on June 15, 1940 to setting up the Lithuanian Activist Front (LAF) in Berlin on November 17, 1940; the second from the formation of Berlin LAF to the beginning of the war between the USSR and Germany on June 22, 1941. The specific feature of the first period is that the events in the summer of 1940 in Lithuania were a stimulus for creation of the first underground organizations. The article reveals the role of the members of the Lithuanian Riflemen’ Union to be abolished while creating the underground, partly evaluating its formation as an attempt of the riflemen to maintain its organizational structures as viable. It is specified that during that period the relations between underground organizations, operating in separate localities, were developed quite weakly, no close cooperation and centres for uniting the underground activity existed. The second period is specified by the fact that after contacts by the Berlin LAF were established with the Lithuanian underground, the relations between the underground organizations in separate localities became strengthened, their close cooperation went on, new underground organizations were created in separate areas; and new members were recruited. The reason was the activity of Berlin, Kaunas and Kretinga organizations in coordinating the Lithuanian underground activity. The coordinating activity of Kretinga underground participants Osvaldas Žadvydas, Jonas Ramanauskas, Petras Bortkevičius and its limits are revealed. Their activity was specific, they had to maintain contacts between Berlin LAF and Lithuanian underground.